Leverage software accessibility features for ADA‐compliant communication. Issue 1 (8th February 2021) - Taylor, Z. W.
Abstract : Communication technologies have made significant advances over the past several decades, including assistive technologies created to help people with disabilities access digital content. In recent years, software developers have updated many common content‐creation software programs to include accessibility options. However, these features are available across several popular software programs only if updates are installed or if users know where to find them, and many of them are tucked away behind several layers of menus. Of the most widely used, affordable, and powerful tools available to content creators working for higher education institutions, the Microsoft Office suite and Adobe Acrobat Pro have the capacity to increase the accessibility of digital content and can help you comply with the Americans with Disabilities Act.